Case report: Daratumumab treatment in pre-transplant alloimmunization and severe hemolytic anemia - Pereda, Maria A.; Hosahalli Vasanna, Smitha; Desai, Neha J.; Deng, Victoria; Owusu-Ansah, Amma; Dallas, Mari H.; Pateva, Irina; Dalal, Jignesh (Frontiers in Immunology, 2022)
Daratumumab, a CD38 monoclonal antibody that has been FDA-approved to treat multiple myeloma, has acquired popularity and is used off-label for both auto- and alloantibody mediated disorders, particularly in refractory/resistant circumstances. Much of the published data for its use in pediatric blood disorders has been in post-transplant autoimmune cytopenias. Here we describe three patients in whom daratumumab was used outside of post-transplant autoimmune cytopenias, highlighting further potential uses of this medication.